Elucidation of Essential and Nonessential Genes in the Haemophilus influenzae Rd Cell Wall Biosynthetic Pathway by Targeted Gene Disruption - Trepod, Catherine M. (American Society for Microbiology, 2005)
Targeted gene disruption by in vitro transposon mutagenesis has been used to identify the genes required for biosynthesis of the Haemophilus influenzae Rd cell wall under standard cultivation conditions. Of the 28 genes known to be associated with the cell wall biosynthetic pathway, 14 were determined to be essential.